PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN UTANG DAN KEBIJAKAN INVESTASI TERHADAP NILAI PERUSAHAAN - Andriani, Rini; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis study is aimed to provide empirical evidences about the influence of dividend policy, debt policy and investment policy to the firm value. The dependent variable in this research is firm value which is measured by using Price Book Value (PBV). The independent variables in this study are measured by using dividend policy,dividend payout ratio (DPR), debt policy is measured by using Debt to Equity Ratio (DER), and investment policy is measured by using Return on Investment (ROI). The population has been obtained by using purposive sampling method on food and beverages companies which are listed in Indonesian Stock Exchange (BEI) in 2012-2015 periods and based on the predetermined criteria 8 food and beverages companies have been selected as samples. The data analysis method has been carried out by using multiple linear regressions and the SPSS (Statistical Product and Service Solutions). The result of theresearch indicates that dividend policy give significant and positive influence to the firm value; debt policy give significant and positive influence to the firm value and investment policy give significant and positive influence to the firm value.Keywords: Dividend policy, debt policy, investment policy, firm value